2020
DOI: 10.1039/d0nr08236h
|View full text |Cite
|
Sign up to set email alerts
|

Microtip focused electrohydrodynamic jet printing with nanoscale resolution

Abstract: Electrohydrodynamic jet (E-Jet) printing is a promising manufacturing technique for micro/nano-patterned structures with high-resolution, high-efficiency and high material compatibility. However, the further improvement of necking ratio of E-jet is still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…This model accurately predicted the effect of applied voltage on jet state, shown in Figure 4a [85]. Su et al showed the diameter of printed droplets decreased with the increase of applied pulse amplitudes, while increased with the increase of applied constant DC voltage [90]. Lee captured the jet state under different amplitude of pulsed voltage [91].…”
Section: Process Parametersmentioning
confidence: 70%
“…This model accurately predicted the effect of applied voltage on jet state, shown in Figure 4a [85]. Su et al showed the diameter of printed droplets decreased with the increase of applied pulse amplitudes, while increased with the increase of applied constant DC voltage [90]. Lee captured the jet state under different amplitude of pulsed voltage [91].…”
Section: Process Parametersmentioning
confidence: 70%
“…The relationship between the droplet diameter and the printing parameters in the pulse mode was studied in our previous work. [ 31 ] The diameter of the printed droplets increased with the enhancement of the pulse amplitude or decrease of the pulse frequency. [ 31 ] In this work, we had successfully fabricated various patterns of MLAs with diameters ranging from submicrometer to micrometer via MFEJ printing through tuning the printing parameters to demonstrate the fabrication possibilities and reproducibility of this technique.…”
Section: Resultsmentioning
confidence: 99%
“…[ 31 ] The diameter of the printed droplets increased with the enhancement of the pulse amplitude or decrease of the pulse frequency. [ 31 ] In this work, we had successfully fabricated various patterns of MLAs with diameters ranging from submicrometer to micrometer via MFEJ printing through tuning the printing parameters to demonstrate the fabrication possibilities and reproducibility of this technique. As shown in Figure a, MLAs with an average diameter of 4.12 ± 0.14 µm were generated on T3 substrate using an ink of NOA 61 UV‐curable polymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous research, we successfully proposed the nanotip-focused electrohydrodynamic jet (NFEJ) printing technique for maskless and direct micro/nanostructure manufacturing with high efficiency and resolution. , This NFEJ printing utilized a solid Ni nanotip rather than a fine microcapillary nozzle, which could extend the printability to different materials and effectively prevent nozzle blockage problems even with high-viscosity printing materials. This technique has also been applied to prepare micro/nanolens arrays (M/NLAs) on the surface of PDMS nanofilm-modified substrate .…”
Section: Introductionmentioning
confidence: 99%